Eighteen-year prospective audit of LASIK outcomes for myopia in 53 731 eyes. Issue 9 (24th October 2018) - Chua, Daniel; Htoon, Hla Myint; Lim, Li; Chan, Cordelia ML; Mehta, Jodhbir S.; Tan, Donald T H; Rosman, Mohamad
Abstract : Background: To assess the outcomes of laser-assisted in situ keratomileusis (LASIK) performed for the treatment of myopia in terms of safety, efficacy and predictability in an 18-year clinical audit. Method: In this single-centre, prospective, non-randomised study, preoperative and postoperative refractions, uncorrected (UCVA), best-corrected Snellen visual acuity (BCVA) and complications of all eyes undergoing myopic LASIK were recorded. Safety, efficacy, refractive predictability, treatment trends, retreatment rates and complication rates were evaluated. Results: Between 1998 and 2015, 53 731 eyes of 27312 patients underwent myopic LASIK. Patients' median age was 31.6 years (mean, 32.6±7.3 years); there were 9703 males (35.5%). Patients were predominantly ethnic Chinese (87.4%). Mean follow-up time was 78±75.6 days (median, 86 days). Overall efficacy index was 0.91 with >99% of eyes achieving UCVA of ≥20/40 and >70% achieving 20/20 since 2010. 95.43% of eyes had no loss of vision postoperatively and 4.2% and 0.37% lost 1 and ≥2 lines BCVA, respectively. From 2010 the safety index has been >1.05. More than 94.0% of eyes achieved within ±1.0 D of target refraction and at least 70% achieved within ±0.50 D of target from 2010 onwards. Retreatment rate was 2.55% and after retreatment 98.4% of eyes achieved ≥20/40 UCVA and 63.5% achieved ≥20/20 UCVA. The overall complication rate is 0.98%, and since 2010, the annual complication rate has been <0.8%. Conclusions: Myopic LASIK performed in Asian eyes is safe and effective with high refractive predictability in a comprehensive LASIK programme with appropriate clinical audit.